Wearable Technology in Sports Monitoring Performance and Health Metrics - Lucas da Silva (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of the research study is to determine the wearable technology in sports. The research determines that monitoring performance also health metrics. Wearable technology has become a common sight in sports, transforming how players prepare, compete, and care for their health. This research investigates the multidimensional influence of wearables on sports performance monitoring and health measures. For measuring, the research study used smart PLS software and AMOS software: the descriptive statistic, correlation coefficient analysis, and the smart PLS Algorithm between them. Wearables have transformed sporting ecosystems, from precision training and injury prevention to data-driven coaching tactics. The ramifications go beyond sports science, impacting long-term athlete development and encouraging a culture of holistic health monitoring. Overall, the research found that wearable technology in sports shows a positive and significant link between them. However, ethical concerns about privacy and equitable access emerge as substantial hurdles. As wearable technology advances, its incorporation with sports promises a future in which human potential is constantly challenged, and the quest for athletic greatness has no bounds.